Symbolism of Resistance and Alternative Identity in the Song 'Keluarga Babi' by Pyong Pyong - Bima Pradipta, Nareswara; Utomo, Udi; Haryono, Slamet (Universitas Syiah Kuala, 2025)
This study explores the symbolic meanings and representations of alternative identity in the song Keluarga Babi by the indie pop-punk band Pyong Pyong from Semarang, Indonesia. The song was selected for its articulation of cultural resistance against social domination and power through the medium of music. Employing a descriptive qualitative approach and symbolic analysis, the research examines how the figures of the pig (babi) and the wolf (srigala) in the lyrics function as social metaphors. The pig symbolizes marginalized groups perceived as inferior but who maintain solidarity, integrity, and courage, while the wolf represents corrupt power structures that oppress the people. The analysis draws on Stuart Halls theory of identity construction, expressivist aesthetics, and Sartrean existentialism to interpret the values of resistance and the courage to choose an alternative way of life. The findings indicate that the song constitutes a form of collective, symbolic, and existential identity expression that challenges domination and celebrates the bravery of being different. This research contributes to the discourse on independent music as a site for the production of cultural meaning and local political resistance.